Formation of Proton Motive Force Under Low-Aeration Alkaline Conditions in Alkaliphilic Bacteria - Matsuno, Toshihide; Goto, Toshitaka; Ogami, Shinichi; Morimoto, Hajime; Yamazaki, Koji; Inoue, Norio; Matsuyama, Hidetoshi; Yoshimune, Kazuaki; Yumoto, Isao (Frontiers in Microbiology, 2018)
In Mitchell’s chemiosmotic theory, a proton (H+) motive force across the membrane (Δp), generated by the respiratory chain, drives ATPase for ATP production in various organisms. The bulk base chemiosmotic theory cannot account for ATP production in alkaliphilic bacteria. However, alkaliphiles thrive in environments with a H+ concentration that is one-thousandth (ca. pH 10) the concentration required by neutralophiles. This situation is similar to the production of electricity by hydroelectric turbines under conditions of very limited water. 　Alkaliphiles manage their metabolism through various strategies involving the cell wall structure and solute transport system and molecular mechanisms on the outer surface membrane. Our experimental results indicate that efficient ATP production in alkaliphilic Bacillus spp. is attributable to a high membrane electrical potential (ΔΨ) generated through an attractive force for H+ on the outer surface membrane. In addition, enhanced ATPase driving force per H+ is derived from the high ΔΨ. However, it is difficult to explain the reasons for high ΔΨ formation based on the respiratory rate. The Donnan effect (which is observed when charged particles that are unable to pass through a semipermeable membrane create an uneven electrical charge) likely contributes to the formation of the high ΔΨ because the intracellular negative ion capacities in alkaliphiles are much higher than those of neutralophiles. There are several variations in adaptation to an alkaline environment in bacteria. To explain the efficient ATP production occurring in H+-less and air-limited environments in alkaliphilic bacteria, we propose a cytochrome c-related “H+ capacitor mechanism” as an alkaline adaptation strategy. As an outer surface protein, cytochrome c-550 from Bacillus clarkii possesses an extra segment rich in Asn content between the region anchored to the membrane and the main body of cytochrome c. This structure may contribute to the formation of the proton-binding network to transfer H+ at the outer membrane surface in obligate alkaliphiles. The H+ capacitor mechanism is elevated even further under low-aeration conditions in both alkaliphilic Bacillus spp. and the gram-negative alkaliphile Pseudomonas alcaliphila.